The Effects of Post-Mating Administration of Anti-IL-10 and Anti-TGF? on Conception Rates in Mice - Risvanli, Ali; Godekmerdan, Ahmet (Royan Inst, 2015)
Background: In fertility studies, it has been shown that transforming growth factor beta (TGF beta) and interlukin 10 (IL-10) play very important roles in implantation, maternal immune tolerance, placentation and fetal development, and the release beginning of release for fetal and postnatal death. The present study aims to determine the effects of the post-mating administration of neutralizing antibodies against IL-10 and TGF beta, which significantly impact pregnancy in females and the conception rates in mice via assessments of blood serum and uterine fluid concentrations of IL-2, IL-4, IL-6, IL-10, IL-17, interferon gamma (IFN gamma), Tumor necrosis factor alpha (TNF alpha), and TGF beta. Materials and Methods: In this experimental study, 21 BALB/c strain female mice were mated and randomly divided into three groups. The mice in the first group were selected as the control group. The second group of animals was injected with 0.5 mg of anti-IL-10 after mating, while those in the third group were intraperitoneally injected with 0.5 mg of anti-TGF beta. The animals in all groups were decapitated on the 13th day after mating and their blood samples were taken. The uteri were removed to determine pregnancy. The mice's uterine irrigation fluids were also obtained. We used the multiplex immunoassay technique to determine the cytokine concentrations in uterine fluid and blood serum of the mice. Results: We observed no intergroup difference with respect to conception rates. A comparison of the cytokine concentrations in the uterine fluids of pregnant mice revealed higher TGF beta concentrations (p<0.01) in the second group injected with the anti-IL-10 antibody compared with the other groups. There was no difference detected in pregnant animals with regards to both uterine fluid and blood serum concentrations of the other cytokines. Conclusion: Post-mating administration of anti-IL-10 and anti-TGF beta antibodies in mice may not have any effect on conception rates.
Keywords: Pregnancy; Mouse; Cytokine